Comparative morphology, anatomy and palynology of two Salvia L. species (Lamiaceae) and their taxonomic implications - Kahraman, Ahmet; Celep, Ferhat; Dogan, Musa (Bangladesh Journal of Plant Taxonomy, 2009)
Morphological, anatomical and palynological characteristics of Salvia glutinosa L. and S. staminea Montbret & Aucher ex Bentham and their taxonomic importance are presented. Their expanded description and phenology are also given. The features of stems, leaves, calyces, corolla and nutlets have been found to be significant to distinguish the species. Mesophyll structure, distribution of stomata on upper epidermis, size of stomata on lower epidermis, shape of vascular structure in midrib, and number of vascular bundles and presence of sclerenchymatic fibers in petiole are diagnostic characters. Moreover, pollen size and exine ornamentation are important in separating these two species. Keywords: Morphology; Anatomy; Palynology; Salvia. DOI: 10.3329/bjpt.v16i1.2749 Bangladesh J. Plant Taxon. 16(1): 73-82, 2009 (June)